(untitled) (Journal of Pathology of Nepal, 2011)
Background: Mutation of the C-KIT oncogene is the central event in gastrointestinal stromal tumors which are the most common mesenchymal tumors arising from the tubular gastrointestinal tract. Materials and Methods: A study was conducted in Patan hospital from April 2003 to May 2010. Mesenchymal tumors arising from the tubular gastrointestinal tract with the microscopic features suggesting gastrointestinal stromal tumor were included in the study. Results: A total of 22 cases were studied. The incidence was highest amongst the older age group (86.36%), than in younger people (13.63%). The tumor most commonly involved the small intestine (54.54%), followed by the stomach (36.36%). Most (59.09%) of the tumors were of huge size measuring >100 mm, and showed necrosis, hemorrhage and cystic degeneration. Mitotic activity was high (>5/50 high power fields) in 55% of the cases. Conclusion: C-KIT immunostaining showed positivity in 19 (86.36%) of the tumors in this study. Mutation of the C-KIT oncogene is seen in most of the gastrointestinal stromal tumors. Keywords: Gastrointestinal; Stromal tumors; C-KIT oncogene DOI: 10.3126/jpn.v1i1.4450 Journal of Pathology of Nepal (2011) Vol.1, 41-44